2008
DOI: 10.1002/ccd.21638
|View full text |Cite
|
Sign up to set email alerts
|

A unique complication of the retrograde approach in angioplasty for chronic total occlusion of the coronary artery

Abstract: The retrograde approach for chronic total occlusion of coronary arteries is a new treatment strategy, although its attendant complications have not yet been fully appreciated. We report a case of isolated left ventricular cardiac tamponade caused by guidewire-induced perforation of the septal branch during the retrograde approach, which was subsequently diagnosed by computed tomography (CT) and which required surgical drainage. Guidewire-induced perforation of the septal branch was successfully treated by auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 20 publications
0
16
1
Order By: Relevance
“…Although there has been no definite consensus on the safety of retrograde PCI for coronary CTO so far, the paucity of published reports has shown the complications of this technique [12,21,22]. In this study, the retrograde approach does not seem to be a completely safe procedure, and we experienced several cases of unexpected complications, such as a dissection or acute thrombosis of the collateral-donor artery, which usually do not happen during the conventional antegrade approach.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Although there has been no definite consensus on the safety of retrograde PCI for coronary CTO so far, the paucity of published reports has shown the complications of this technique [12,21,22]. In this study, the retrograde approach does not seem to be a completely safe procedure, and we experienced several cases of unexpected complications, such as a dissection or acute thrombosis of the collateral-donor artery, which usually do not happen during the conventional antegrade approach.…”
Section: Discussioncontrasting
confidence: 56%
“…In this study, septal perforation occurred in several cases without affecting the clinical course. This emphasizes that the septal channel is a safer retrograde access route than the epicardial channel although there are few case reports about complications related to the septal collateral perforation [21,22]. If the epicardial collateral is used for retrograde access and this collateral constitutes a major feeding route for target vessel, which is frequently seen in well-developed epicardial collateral cases, careful manipulation of the retrograde device is required because injury to the epicardial collateral potentially can bring about serious complications such as pericardial tamponade or extensive target vessel ischemia.…”
Section: Discussionmentioning
confidence: 97%
“…Intravascular ultrasounddetected coronary hematomas have been shown to be associated with an increased rate of non-Q-wave myocardial infarction and need for repeat revascularization if appropriate treatment (e.g., coverage by stenting) was not performed (30). Some of these injuries (e.g., IVUS-detected extramural coronary hematoma or perforation) can evolve to angiographic free perforation either directly from guidewire manipulation or from subsequent ballooning or stenting (31,32). One recent IVUS report indicated that subintimal drug-eluting stent implantation during a CTO-PCI caused multiple late-acquired malappositions due to coronary aneurysm formation (33).…”
Section: Discussionmentioning
confidence: 97%
“…For example, Matsumi et al reported a patient with isolated cardiac tamponade caused by guidewire-induced perforation of the septal branch during a retrograde approach. 1 The perforation was successfully treated by autologous subcutaneous tissue embolization of the coronary artery. Similarly, Fischell et al reported two patients with guidewirerelated distal coronary artery perforation who were successfully treated by localized distal intracoronary thrombin injection.…”
Section: Fig 2 Operative Fi Ndings Amentioning
confidence: 99%